Resistance of polylactic acid/nanofibrillated cellulose composite to scratching - Poljanšek, Ida (Les (Ljubljana), 2019)
The aim of the study was to prepare a bionanocomposite based on polylactic acid (PLA) with the addition of nanofibrillated cellulose (NFC) as a reinforcement component. For the production of the composite we used unmodified and acetylated NFC (A_NFC). Freeze-dried NFC was acetylated in a heterogeneous system with acetic anhydride in di- methylformamide (DMF) in the presence of pyridine as a catalyst. The success of the acetylation was determined by FT-IR spectroscopy. PLA films were prepared with the addition of 2.5 %, 5 % and 10 % of unmodified and acetylated NFC. The focus of this research was the impact of the NFC additive on the transparency and on the resistance of the biona- nocomposite to scratching. The transparency of the bionanocomposite film was measured using UV-Vis spectrophoto- metry, and the resistance of the films to scratching was evaluated with a scratch test. The optimal amount of NFC and A_NFC added to the polymer PLA to achieve better resistance of the bionanocomposite to scratching was determined. The best resistance of the prepared bionanocomposite to scratching was achieved by the addition of a 2.5 % A_NFC to the PLA polymer, which also has minimal reduced transparency with respect to the PLA film. With the highest addition of A_NFC to the PLA polymer, bionanocomposite films with minimal reduction of transparency were obtained.
Keywords: bionanocomposite; bionanokompozit; nanofibrilirana celuloza; nanofibrillated cellulose; odpornost proti razenju; PLA; prosojnost; resistance to scratching; transparency